2017
DOI: 10.1093/annonc/mdx503
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in pancreatic ductal adenocarcinoma: an emerging entity?

Abstract: The genomic-plasticity of the immune system creates a broad immune repertoire engaged to tackle cancer cells. Promising clinical activity has been observed with several immune therapy strategies in solid tumors including melanoma, lung, kidney, and bladder cancers, albeit as yet immunotherapy-based treatment approaches in pancreatic ductal adenocarcinoma (PDAC) remain to have proven value. While translational and early clinical studies have demonstrated activation of antitumor immunity, most recent late-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 76 publications
0
71
0
Order By: Relevance
“…Surgical removal and FOLFIRINOX chemotherapy are common treatment strategies for PDAC (44). Surgical removal is typically available to only 10%-15% of patients with PDAC (45). FOLFIRINOX can improve patient survival, but because of its toxicity FOLFIRINOX cannot be universally applied to all patients with PDAC (44,46).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical removal and FOLFIRINOX chemotherapy are common treatment strategies for PDAC (44). Surgical removal is typically available to only 10%-15% of patients with PDAC (45). FOLFIRINOX can improve patient survival, but because of its toxicity FOLFIRINOX cannot be universally applied to all patients with PDAC (44,46).…”
Section: Discussionmentioning
confidence: 99%
“…[5] However, unfortunately, these approaches including immunotherapy have achieved limited success in the management of PDAC due in part to its distinct molecular behavior. [6,7] For example, immune checkpoint inhibitors have been shown to be effective in patients with mismatch repair de cient (MMR-D) PDAC [8], which accounts for about one percent of PDAC cases. [9,10] Recently, a phase III trial of olaparib, a poly (ADP-ribose) polymerase (PARP) inhibitor, reported improvement in progression-free survival (PFS) in BRCA-mutant metastatic PDAC patients when administered as maintenance therapy following platinum-based treatment, compared to placebo.…”
Section: Background and Materialsmentioning
confidence: 99%
“…The mechanisms underlying the resistance of pancreatic cancer to the antitumor immune response have been extensively reviewed and are largely attributed to perturbations in immune surveillance, the process of immunoediting, and immune privilege [13,[59][60][61]. Although pancreatic cancer has been relatively resistant to singleagent checkpoint blockade when compared to more immune sensitive tumors, strategies for overcoming primary resistance to immunotherapy in pancreatic cancer are readily available from investigations in other solid tumor types focused on improving the antitumor efficacy of checkpoint blockade through combining various therapeutic modalities on a checkpoint inhibitor backbone [62][63][64].…”
Section: Mechanisms Of Immune Resistance and Rational Combination Strmentioning
confidence: 99%
“…Other tumor cell-intrinsic and tumor cell-extrinsic mechanisms of resistance to immune checkpoint inhibitors in pancreatic cancer include (1) the ability of pancreatic cancer cells to evade the host antitumor immune response (immunoediting) through expression of immune checkpoints such as PD-L1 and indoleamine-2,3-dioxygenase (IDO), secretion of granulocyte-macrophage colony-stimulating factor (GM-CSF) resulting in a myeloid cell-inflamed phenotype, and upregulation of regulatory T-cells (Tregs) and (2) induction of immune tolerance by direct interaction between cancer cells and tumor antigen-specific T-cells (immune privilege) through downregulation of antigen presenting major histocompatibility complex (MHC) molecules, expression of Fas ligand and decreased Fas receptor signaling, and expression of Foxp3 [13,14].…”
Section: Introductionmentioning
confidence: 99%